2022
DOI: 10.1155/2022/2938340
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] The Fertility Status of the Married People Living with HIV/AIDS in China

Abstract: In order to analyze the fertility status of the married people living with human immunodeficiency virus (HIV)/acquired immune deficiency syndrome (AIDS) (PLHA) of reproductive age in China, a sample of married PLHAs aged 22–45 in China is selected by using a stratified cluster sampling method. All participants are face-to-face interviewed with a structured questionnaire. Among them, the fertility status and its influencing factors of 366 PLHAs are statistically analyzed. Experimental results show that married … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“… 7 A previous study in China revealed that one-fifth of CLWH had the intention to have a child. 8 Among CLWH, there were interpersonal and social factors such as gender expectations for women to bear child and the desires of partners for the women to have a child influence women’s desire to conceive. 9 A systematic review revealed that dominance of women incongruency, women empowerment, was positively associated with the ability to make fertility decisions and increase spousal communication.…”
Section: Introductionmentioning
confidence: 99%
“… 7 A previous study in China revealed that one-fifth of CLWH had the intention to have a child. 8 Among CLWH, there were interpersonal and social factors such as gender expectations for women to bear child and the desires of partners for the women to have a child influence women’s desire to conceive. 9 A systematic review revealed that dominance of women incongruency, women empowerment, was positively associated with the ability to make fertility decisions and increase spousal communication.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%